Chronic disease patients during the armed conflict in Sudan: a cross-sectional study on mental health and quality of life - Sohaib Mohammed Mokhtar Ahmed; Moram Elfadel Abdelrhaman Gasmalha; Ahmed Balla M. Ahmed; Khalid Abusofyan Eljezoli Mohammed; Salma Alrawa; Hebatallah Fadhl; Mohanned Abdalsalam Mohammed Salih; Israa Alamin Mohammed Hussein; Asma Mohammed Ahmed Mohammed Salih; Haifa Ibnomer Abdelrahman Elsharif; Hiba Atif Ahmad Elhussein; Sajda Abdelaziz Yahya Abaker; et al. (Conflict and Health)
Abstract Background Chronic diseases represent a major global health burden, with their impact becoming even more pronounced in conflict settings. In such environments, the mental health and quality of life of chronic disease patients often deteriorate due to the disruptions caused by war. This study aimed to assess mental health issues among chronic disease patients and evaluate their quality of life during the ongoing armed conflict in Sudan. Methods A cross-sectional study was conducted among chronic disease patients in the safest states of Sudan during the current war. Mental health was assessed with the Patient Health Questionnaire-9 for depression and Generalized Anxiety Disorder-7 for anxiety, and quality of life was evaluated using the EuroQol 5-Dimension 5-Level scale. Chi-square tests and Spearman’s rank examined associations between socio-demographic factors and mental health outcomes. Multiple linear regression identified predictors influencing mental health issues, with statistical significance set at p ≤ 0.05. Results Among 1116 chronic disease patients, the median depression score was 7 (IQR = 8), with 50.3% reporting mild to moderate depression, while the median anxiety score was 6 (IQR = 8), with 47.1% experiencing mild to moderate anxiety. Depression showed significantly strong positive correlation with anxiety (ρ = 0.810, p < 0.00). In terms of health-related quality of life, the pain/discomfort domain showed 40.7% of patients reporting moderate to extreme problems, followed by the anxiety/depression domain at 43.4%, making these the most affected areas. Conclusion This study revealed high levels of depression and anxiety among Sudanese chronic disease patients during the war, alongside a notably poor quality of life. The findings underscore the urgent need for intervention to implement targeted mental health support programs, aiming to improve the quality of life for this vulnerable population.